2019
DOI: 10.5294/aqui.2019.19.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Strategies on the Sleep Quality of People with Diabetes: Randomized Clinical Trial

Abstract: Objective: To evaluate the effect of educational strategies on sleep quality and its relation to diabetes-related distress and glycemic control in people with type 2 diabetes mellitus (DM2). Materials and methods: Randomized clinical trial involving two groups. Group 1 (G1, n = 45) received verbal guidance and leaflets on sleep hygiene strategies and group 2 (G2, n = 46) received usual health care guidelines on self-care with the feet. Sleep was assessed by the Pittsburgh Sleep Quality Inventory and diabetes-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
8
0
3
Order By: Relevance
“…One study [ 67 ] in people with type 2 diabetes and late sleeping times showed that sleep education improved sleep quality and reduced HbA 1c (−1.5 ± 0.55 mmol/mol [−2.29 ± 2.20%] vs −1.11 ± 0.47 mmol/mol [−2.25 ± 2.19%]; p < 0.05), compared with controls. The other study [ 68 ] investigating people with type 2 diabetes and abnormal or poor sleep, reported improved sleep after sleep education but no change in glycaemic control. Overall, these studies suggest that both CBT-I and sleep education could contribute to improving sleep and health outcomes in those with type 2 diabetes and sleep disorders.…”
Section: Treating Sleep Disorders In Type 2 Diabetesmentioning
confidence: 99%
“…One study [ 67 ] in people with type 2 diabetes and late sleeping times showed that sleep education improved sleep quality and reduced HbA 1c (−1.5 ± 0.55 mmol/mol [−2.29 ± 2.20%] vs −1.11 ± 0.47 mmol/mol [−2.25 ± 2.19%]; p < 0.05), compared with controls. The other study [ 68 ] investigating people with type 2 diabetes and abnormal or poor sleep, reported improved sleep after sleep education but no change in glycaemic control. Overall, these studies suggest that both CBT-I and sleep education could contribute to improving sleep and health outcomes in those with type 2 diabetes and sleep disorders.…”
Section: Treating Sleep Disorders In Type 2 Diabetesmentioning
confidence: 99%
“…Para a população com diabetes este dado é preocupante, pois impacta em seu bem estar físico e mental, uma vez que a manutenção quantitativa do sono deficitária, ao provocar elevação do cortisol, causa interferência no metabolismo da glicose e no controle glicêmico (Pereira, Trevisan, Lourenço, Silva & Lima, 2019).…”
Section: Resultsunclassified
“…A metodologia utilizada foi um estudo de caso descritivo, qualitativo, quantitativo, exploratório e inferencial, tendo como cenário a pandemia do COVID-19 nas rotinas odontológicas no Brasil. O estudo de caso na área da saúde tem a finalidade de investigar analisar e descrever um fenômeno de forma a validar uma pesquisa científica (PEREIRA et al,2019).O Estudo de caso pode ser considerado complexo e completo; pois descreve, analisa e observa dados: qualitativos e quantitativos. Segundo Yin (2015) dados qualitativos e qualitativos são complementares em um amplo estudo investigativo.…”
Section: Metodologiaunclassified
“…Os aspectos desta dimensão frequentemente podem estar associados, de forma causal, a dimensão decréscimo de energia vital, que neste estudo identificou a dificuldade para dormir como um achado, principalmente na população adulta. Para a população com diabetes este dado é preocupante, pois impacta em seu bem estar físico e mental, uma vez que a manutenção quantitativa do sono deficitária, ao provocar elevação do cortisol, causa interferência no metabolismo da glicose e no controle glicêmico (PEREIRA et al, 2019).…”
Section: A Vida Dos Indivíduos Com Diabetes Mellitus Durante a Pandemia De Covid-19unclassified